Using Augmented Reality (AR) in Creating Digital Art Magazine to Promote Malaysian Arts: An Augmented Reality Mobile Application in magazine to Promote Malaysian Arts - Atiqah Norizan; Zuriani Ab Ghani (Journal of Computing Technologies and Creative Content, 2022)
Malaysia is a country full of Malaysian artists that draws the heart of Malaysia into spectacular painting and people need to appreciate it with full of concentration and open minds and observe it. Augmented Reality Mobile Application was developed for this research. Augmented Reality has existed in around the world and it became useful for many industries to be achieved. Therefore, in order to appreciate the art and the artist achievement is to develop magazine for Malaysia and to exist an Augmented Reality (AR) app in creating digital art magazine in Malaysia. It is developed as an approach to make life easier and to attract younger generation in Malaysia as an era nowadays people used smartphones around the world as it become important in daily life. The research methodology used ADDIE model and the testing has been conducted with 48 respondents. Based on the results, it shows that the user have heard of Augmented Reality (AR) before and majority of people has strongly agreed of the contents that bring arts come alive and majority has most agreed to continue Augmented Reality (AR) in the future.